2016
DOI: 10.1016/j.scienta.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Fruit characteristics and cuticle triterpenes as related to postharvest quality of highbush blueberries

Abstract: Està subjecte a una llicència de Reconeixement-NoComercial-SenseObraDerivada 4.0 de Creative Commons Elsevier Editorial System(tm) for Scientia Horticulturae Manuscript Draft

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 48 publications
6
60
1
Order By: Relevance
“…Reduction in the turgor is likely due to the accumulation of osmotic solutes in the apoplast and to water loss by the fruit [41] and has been reported in stored blueberries [75]. Recent studies have also shown the roles of the stem scar size/transpiration and cuticular wax composition and thickness in water loss and maintenance of the post-harvest firmness in blueberry [22,76,77]. Among the blueberry fruit cuticular triterpenoid composition, the ursolic acid content at harvest was positively correlated to weight loss and softening after storage, offering an interesting target for further studies [77].…”
Section: Molecular and Architectural Changes In Plant Cell During Frumentioning
confidence: 88%
See 1 more Smart Citation
“…Reduction in the turgor is likely due to the accumulation of osmotic solutes in the apoplast and to water loss by the fruit [41] and has been reported in stored blueberries [75]. Recent studies have also shown the roles of the stem scar size/transpiration and cuticular wax composition and thickness in water loss and maintenance of the post-harvest firmness in blueberry [22,76,77]. Among the blueberry fruit cuticular triterpenoid composition, the ursolic acid content at harvest was positively correlated to weight loss and softening after storage, offering an interesting target for further studies [77].…”
Section: Molecular and Architectural Changes In Plant Cell During Frumentioning
confidence: 88%
“…Recent studies have also shown the roles of the stem scar size/transpiration and cuticular wax composition and thickness in water loss and maintenance of the post-harvest firmness in blueberry [22,76,77]. Among the blueberry fruit cuticular triterpenoid composition, the ursolic acid content at harvest was positively correlated to weight loss and softening after storage, offering an interesting target for further studies [77]. The importance of containing water loss is also supported by the fact that coating fruits with oily films, which create a semi-permeable barrier around the fruit, prevented firmness decay [78,79].…”
Section: Molecular and Architectural Changes In Plant Cell During Frumentioning
confidence: 99%
“…Reduction in the turgor is likely due to the accumulation of osmotic solutes in the apoplast and to water loss by the fruit [41] and has been reported in stored blueberries [74]. Recent studies had also shown the roles of the stem scar size/transpiration and cuticular wax composition and thickness in water loss and maintenance of the post-harvest firmness in blueberry [22,75,76]. Among the blueberry fruit cuticular triterpenoid composition, the ursolic acid content at harvest was positively correlated to weight loss and softening after storage, offering an interesting target for further studies [76].…”
Section: Gh 17 Family Members Have Been Associated With Cell Wall Degmentioning
confidence: 88%
“…Recent studies had also shown the roles of the stem scar size/transpiration and cuticular wax composition and thickness in water loss and maintenance of the post-harvest firmness in blueberry [22,75,76]. Among the blueberry fruit cuticular triterpenoid composition, the ursolic acid content at harvest was positively correlated to weight loss and softening after storage, offering an interesting target for further studies [76]. The importance of containing water loss is also supported by the fact that coating fruits with oily films, which create a semi-permeable barrier around the fruit, prevented firmness decay [77,78].…”
Section: Gh 17 Family Members Have Been Associated With Cell Wall Degmentioning
confidence: 99%
“…Among them, and regardless of season, dehydration and softening are the most common defects causing shipment rejections (Moggia et al, 2016b). …”
Section: Introductionmentioning
confidence: 99%